Optical encryption using phase-shifting interferometry in a joint transform correlator - La Mela, Cecilia (2006)
We propose an optical encryption technique where the encrypted field and the decrypting key are obtained by three-step phase-shifting interferometry and registered as digital Fresnel holograms in a joint transform correlator architecture. Decryption can be achieved by digital or optical means. The technique allows the complete process to be achieved at high speed and data to be transfered via digital communication channels. Experimental implementation is performed in a system based on a programmable liquid-crystal TV display working in pure phase mode to represent the input data and to introduce the required phase shifts. A CCD is used to register the output data.